Pseudomonas aeruginosa infection in cystic fibrosis: pathophysiological mechanisms and therapeutic approaches. (2nd June 2016) - Lund-Palau, Helena; Turnbull, Andrew R.; Bush, Andrew; Bardin, Emmanuelle; Cameron, Loren; Soren, Odel; Wierre-Gore, Natasha; Alton, Eric W. F. W.; Bundy, Jacob G.; Connett, Gary; Faust, Saul N.; Filloux, Alain; et al.
ABSTRACT: Pseudomonas aeruginosa is a remarkably versatile environmental bacterium with an extraordinary capacity to infect the cystic fibrosis (CF) lung. Infection with P. aeruginosa occurs early, and although eradication can be achieved following early detection, chronic infection occurs in over 60% of adults with CF. Chronic infection is associated with accelerated disease progression and increased mortality. Extensive research has revealed complex mechanisms by which P. aeruginosa adapts to and persists within the CF airway. Yet knowledge gaps remain, and prevention and treatment strategies are limited by the lack of sensitive detection methods and by a narrow armoury of antibiotics. Further developments in this field are urgently needed in order to improve morbidity and mortality in people with CF. Here, we summarize current knowledge of pathophysiological mechanisms underlying P. aeruginosa infection in CF. Established treatments are discussed, and an overview is offered of novel detection methods and therapeutic strategies in development.